Sense of support within the family: a cross-sectional study of family members in palliative home care - Anna Milberg; Maria Liljeroos; Rakel Wåhlberg; Barbro Krevers (BMC Palliative Care, 2020)
Abstract Background Despite evidence that family members’ support to each other can be of importance to its members, there are limited studies of factors related to family members’ sense of such support during palliative care. Aim Based on the family systems approach, we evaluated which factors were associated with family members’ sense of support within their closest family in a palliative home care context and developed a model that predicts such sense of support. Design A cross-sectional design was used. We interviewed 209 adult family members (69% of eligible) of adult patients with expected short survival receiving palliative home care. Methods Generalised linear models were used to evaluate individual factors related to family members’ sense of support within their closest family during palliative care. The Akaike Information Criterion (AIC) was applied in the model-building analyses. Results Nineteen variables were identified that were significantly associated with the family members’ sense of support within the closest family. Model building selected six variables for predicting this sense of support (decreasing Wald values): family member perceiving support from other more distant family members; feeling secure with the provided palliative home care; possibility of respite if family member needed a break; family member living alone; being a child of the patient (inverse relationship); perceiving that the patient was supported by other family members. Conclusions Our findings support clinical application of the Family Systems Theory in the context of palliative care. The factors identified may be of value in assisting practitioners in detecting and treating family members sensing a low level of support within the closest family.